Accounting Information Systems and Business Performance: A Systematic Literature Review - Maulina, Baiq Farida; Nazaruddin, Ietje (Journal of Accounting and Investment, 2025)
Research aims: This study aims to evaluate journals discussing Accounting Information Systems on Business Performance to identify lessons that may be useful for addressing similar situations in the future.Design/Methodology/Approach: This study employs a review procedure adapted from Hoque (2014), including keyword analysis to map out themes. The journals to be reviewed were identified by using the search keywords "Accounting" AND "Information" AND "System*" and "Business Performance*". After applying a set of criteria, 58 journals were included in the subsequent analysis. The countries of origin, the findings obtained, and the lessons learned are further discussed.Research findings:  The study generated four research themes based on the analyzed literature: (1) Innovation Performance – the role of innovation strategies in improving business productivity and growth; (2) Innovation Capability – the importance of integrating knowledge and resources to enhance innovation processes; (3) Government Regulation – the impact of financial support and training programs on business growth; and (4) Competitive Advantage – the role of strategic management in achieving superior business performance in dynamic market environments.Theoretical contribution/ Originality: This study analyzes and uncovers key themes in the integration of Accounting Information Systems (AIS) and business performance, highlighting emerging trends such as innovation capability, government regulation, and competitive advantage. It identifies gaps in current research related to the adoption of new technologies like blockchain, AI, and cloud-based systems. Additionally, the study provides future research directions focusing on security, sustainability practices, and the evolving role of AIS in enhancing strategic decision-making and operational efficiency.Practitioner/Policy implication: This study can be used by business leaders to enhance decision-making through effective implementation of Accounting Information Systems (AIS), by governments to design supportive regulations and financial assistance programs for business growth, and by academics to develop frameworks for integrating technological innovations like blockchain, AI, and cloud computing into AIS for improved business performance and competitiveness.Research limitation/Implication: Future research is expected to examine: (1) The integration of blockchain technology to enhance transparency and reliability in Accounting Information Systems (AIS); (2) The adoption of AI and machine learning for automating accounting processes and detecting financial fraud; (3) The impact of cloud-based AIS on data security and collaboration; (4) The use of big data analytics for financial forecasting and risk management; (5) The role of AIS in supporting Environmental, Social, and Governance (ESG) reporting; and (6) The influence of government regulations on AIS implementation and business performance.